2012
DOI: 10.4028/www.scientific.net/kem.504-506.895
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Analysis of the Process Behaviour of Advanced High Strength Steels in Bending and Shearing Operations

Abstract: In the automotive sector the application of advanced high strength steels (AHSS) for structural and safety relevant components plays an important role. Typical manufacturing processes concerning these parts are bending and cutting operations. However, the forming and cutting potential of these steel grades is different compared to conventional steels, as the process behaviour is changing. For an improved workpiece quality the fundamental knowledge of the damage and failure mechanisms is essential. This study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A calibration of the damage model`s parameters with experiments, where observable failure occurs, usually has to be performed in this case. However, it could be shown that also a strain based identification method is appropriate to adapt the damage parameters to bending experiments, when no observable failure occurs [14]. A methodology was developed to derive the maximum major strain φ max at the outer surface of the bending edge utilizing an optical strain measurement system and the progression of the strain curve over the displacement of the punch is used as a target function for the optimisation process.…”
Section: Parameter Identification and Adaption Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…A calibration of the damage model`s parameters with experiments, where observable failure occurs, usually has to be performed in this case. However, it could be shown that also a strain based identification method is appropriate to adapt the damage parameters to bending experiments, when no observable failure occurs [14]. A methodology was developed to derive the maximum major strain φ max at the outer surface of the bending edge utilizing an optical strain measurement system and the progression of the strain curve over the displacement of the punch is used as a target function for the optimisation process.…”
Section: Parameter Identification and Adaption Strategymentioning
confidence: 99%
“…As starting values the determined parameters of the uniaxial tensile test are used and systematically varied. Within the study of [14] the methodology was proved for the micromechanical damage model of Gurson [4] and for the case that no failure in terms of cracks occurs in the bending experiments with high strength low alloyed steels with a sheet thickness of t 0 = 1.8 mm. The aim of the present study is to show that the strain based calibration method is appropriate to determine and adapt Lemaitre [3] damage parameters to bending load cases with the different steel grade AHSS and a different sheet thickness of t 0 = 1.0 mm.…”
Section: Parameter Identification and Adaption Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a damage prediction system requires an investigation of parameters determining the process and their effect on the formability. In a first step the bendability and the cutting behaviour are analysed in new constructed model experiments [6]. Within the model tests process defining parameters can be varied and thus the damage evolution of the material can be studied in dependency of these parameters experimentally.…”
Section: Experimental and Numerical Analysis Of Damage Behaviour In B...mentioning
confidence: 99%
“…5. Preliminary investigations showed [6], that more critical bending conditions occur, when the bending line is orientated parallel to the rolling direct of the sheet. Consequently, the validation of the damage prediction programme is demonstrated for this parameter set.…”
Section: Experimental Validation Of Damage Prediction Programmementioning
confidence: 99%